A Socio-Seismology Experiment in Haiti - Calais, Eric; Boisson, Dominique; Symithe, Steeve; Prépetit, Claude; Pierre, Bétonus; Ulyse, Sophia; Hurbon, Laennec; Gilles, Alain; Théodat, Jean-Marie; Monfret, Tony; Deschamps, Anne; Courboulex, Françoise; et al. (Frontiers in Earth Science, 2020)
Earthquake risk reduction approaches classically apply a top-down model where scientific information is processed to deliver risk mitigation measures and policies understandable by all, where end-users are shielded from the initial, possibly complex, information. Alternative community-based models exist but are rarely applied at a large scale and rely on valuable, but non-scientific, observations and experiences of local populations. In spite of risk reduction efforts based on both approaches, changes in behavior or policies are slow or even non-existent, in particular in developing countries. Here we report on the initial stage of a project that aims at testing, through a participatory seismology experiment in Haiti – a country struck by a devastating earthquake in January 2010 – whether public or community involvement through the production and usage of seismic information can improve earthquake awareness and, perhaps, induce grassroots protection initiatives. This experiment is made possible by the recent launch of very low-cost, plug-and-play, Raspberry Shake seismological stations, the relative ease of access to the internet even in developing countries such as Haiti, and the familiarity of all with social networks as a way to disseminate information. Our early findings indicate that (1) the seismic data collected is of sufficient quality for real-time detection and characterization of the regional seismicity, (2) citizens are in demand of earthquake information and trust scientists, even though they appear to see earthquakes through the double lens of tectonics and magic/religion, (3) the motivation of seismic station hosts has allowed data to flow without interruption for more than a year, including through a major political crisis in the Fall of 2019 and the current COVID19 situation. At this early stage of the project, our observations indicate that citizen-seismology in a development context has potential to engage the public while collecting scientifically-relevant seismological information.